Qada’ dan Qadar dan Implementasi Dalam Kehidupan - Adinda, Febby; Samudra, Bintang Arif; Karim, Pangulu Abdul (ANWARUL, 2025)
Life in this world is filled with various kinds of experiences that have been determined by Allah SWT in the book Lauhul Mahfudz. Every event, whether pleasant or sad, is a manifestation of divine destiny that cannot be changed. Natural disasters such as earthquakes, tsunamis and floods that often hit our nation are part of His will and power. This belief in destiny provides calm and prevents a believer from feeling frustrated and arrogant. Death, birth, fortune, soul mate, as well as happiness and misery have been determined according to His provisions which are unknown to humans. Therefore, understanding qadha and qadar is very important in everyday life. True faith includes six pillars of faith, including belief in God's destiny, both good and bad. Misunderstandings about destiny can damage a person's faith. Through this discussion, we want to explore the concept of qadha and qadar and its implementation in everyday life, as a step towards becoming a devout servant and achieving the highest goal in Islam: seeing Allah and becoming a resident of heaven.